Chronic low back pain and postural instability: interaction effects of pain severity, age, BMI, and disability - Adel Alshahrani; Ravi Shankar Reddy; Sunil Kumar Ravi (Frontiers in Public Health)
ObjectivesThis study aimed to (1) compare postural sway patterns between individuals with chronic low back pain (CLBP) and asymptomatic controls, (2) evaluate correlations between pain severity and postural stability variables, and (3) assess the interaction effects of age, BMI, pain severity, and disability on postural stability under eyes-open and eyes-closed conditions.MethodsPostural stability (sway area, sway velocity, CoP displacement) was assessed in 88 CLBP patients and 88 controls using a stabilometric platform. Pain severity (VAS) and disability (ODI) were recorded alongside demographic data. Statistical analyses included t-tests, Pearson’s correlations, and ANOVA to explore group differences, correlations, and interaction effects.ResultsChronic low back pain patients exhibited significantly greater postural sway across all conditions, with larger sway area (16.80 ± 6.10 cm2 vs. 11.50 ± 4.10 cm2, p = 0.004) and higher sway velocity (4.10 ± 1.40 cm/s vs. 2.90 ± 1.00 cm/s, p = 0.009) under eyes-closed conditions. Pain severity correlated with sway velocity (r = 0.52, p = 0.003) and CoP displacement (r = 0.57, p = 0.002). Interaction effects indicated greater instability in older, obese individuals with severe pain and high disability.ConclusionChronic low back pain is associated with impaired postural stability, influenced by pain severity, BMI, age, and disability. Targeted interventions addressing these factors are essential for improving balance and reducing fall risk.